Proteção de dados pessoais: uma análise sobre a aplicabilidade do legítimo interesse - Glitz, Gabriela Pandolfo Coelho (2019)
This paper seeks to address the theme of the right to the protection of personal data within the Brazilian legal system, focusing on the figure of legitimate interest. To this end, it begins with an analysis of the history and conceptual developments brought about by the network society and the impacts of this society on the protection of personal data. Subsequently, the objective is to demonstrate the three paradoxes of electronic fortress and the impacts that this evolution has brought on the protection of the right to the protection of personal data. Faced with this new social context, the analysis of the limit and scope of legitimate interest within the personal data protection system begins. To this end, it begins with brief considerations on the fundamental right to the protection of personal data. Then, we discuss the problem of general clauses and the impacts of legal transplants on the Brazilian legal system. Finally, this paper addresses the application format of legitimate interest in Europe and the possible developments in Brazil through LGPD. Thus, the main theme of this work is the problematic of the application of legitimate interest in Brazil, having as research hypothesis the European context of the applicability of legitimate interest as a guide for the application to Brazilian law, passing this hypothesis through a whole process. analysis of the limit and scope of the legitimate interest in this legislation and its relationship with the protection of the fundamental right to the protection of personal data. Thus, it is concluded that a transparent and thoughtful application of the legitimate interest in LGPD is possible, based on the European experience and the balance between the rights and freedoms of data subjects against the legitimate interests of controllers.